RESPON SISWA TERHADAP PEMBELAJARAN MATEMATIKA REALISTIK DENGAN KONTEKS BUDAYA BATAK TOBA - Sinta Dameria Simanjuntak; Imelda Imelda (MES: Journal of Mathematics Education and Science, 2018)
Abstract. The problem examined in this study is how students respond to realistik mathematics education that uses the context of Toba Batak culture in teaching and learning activities. The aim of the researcher to analyze students' responses to realistik mathematics education using the context of the Toba Batak culture is to find out whether the responses given by students are positive or negative. Student responses are said to be positive if students feel happy about the components of learning used, the learning component used is new, students are interested in carrying out the same learning in later learning and students are interested in the learning components used. The research results obtained are students giving positive responses to realistik mathematics education using the context of Toba Batak culture. In other words, students happy with the components of learning, the learning component used is new, students are interested in carrying out the same learning in later learning and students are interested in the learning components used.Keywords: RME, Responses, Toba Batak Culture